Penilaian Kesiapsiagaan Bencana Pusat Kesehatan Masyarakat (Puskesmas) di Indonesia Menggunakan Indeks Keamanan Rumah Sakit - J EL Matury, Herlina; Lestari, Fatma; Baharuddin, Mohd Rafee B; Syahlan, Nabila (Journal of Health Science and Prevention, 2026)
This study evaluated the disaster preparedness of Public Health Centres (PHCs) in terms of structural safety, non-structural safety, and emergency and disaster management capacity. Ensuring that healthcare facilities remain functional during emergencies is essential for maintaining service continuity, particularly in disaster-prone regions such as Indonesia. This cross-sectional descriptive study was conducted in 2024 across 14 PHCs located in disaster-prone areas of North Sumatra Province, Indonesia. A total of 70 participants were involved, with five staff members selected from each PHC based on their roles in facility management and disaster preparedness. Data were collected using structured observations, interviews, checklists, and document reviews based on the Hospital Safety Index (HSI) framework. Ethical approval was obtained from the Faculty of Public Health, Universitas Indonesia, and informed consent was secured from all participants. The safety index scores ranged from 0.2394 (23.94%) to 0.7234 (72.34%), with PHC C achieving the highest score and PHC I the lowest. Functional preparedness consistently emerged as the weakest component across most PHCs, indicating significant challenges in maintaining essential health services during emergencies. PHCs located in Medan City and North Padang Lawas Regency demonstrated higher preparedness levels compared to those in Toba and Padang Lawas Regencies. Disaster preparedness among PHCs varied considerably across regions, with functional capacity identified as the most critical area requiring improvement. Strengthening operational readiness and integrating disaster preparedness into routine health system management are essential to enhance resilience. Future research should evaluate the effectiveness of long-term interventions and explore the role of community engagement in disaster preparedness.